2015
DOI: 10.1134/s1021443715020132
|View full text |Cite
|
Sign up to set email alerts
|

Effects of far red light on the induction changes of prompt and delayed fluorescence and the redox state of P700 in Scenedesmus quadricauda

Abstract: The spectral composition of sunlight in natural aquatic habitats depends on the depth of submer gence and the solar time. Changes in the fractional amount of far red light (FRL) in the total photon flux are associated with the redistribution of light energy absorbed by the two photosystems of photosynthesis. Exper iments with a culture of Scenedesmus quadricauda revealed the influence of FRL preillumination on photo synthetic electron transport and associated processes in microalgae. The plant efficiency analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…The average chlorophyll content in the cells pelleted on filters was ~400 mg/m 2 , which was comparable to its content in leaves of vascular plants (approximately 500 mg/m 2 ) [10]. Control measurements of fluorescence on cell suspensions of Scenedesmus quadricauda using an Aqua-Pen-C (AP-C 100) fluorometer (Photon Systems Instruments, Czech Republic) have shown that the procedure of concen-trating samples on filters had no influence on cell physiological condition [9].…”
Section: Methodsmentioning
confidence: 87%
See 1 more Smart Citation
“…The average chlorophyll content in the cells pelleted on filters was ~400 mg/m 2 , which was comparable to its content in leaves of vascular plants (approximately 500 mg/m 2 ) [10]. Control measurements of fluorescence on cell suspensions of Scenedesmus quadricauda using an Aqua-Pen-C (AP-C 100) fluorometer (Photon Systems Instruments, Czech Republic) have shown that the procedure of concen-trating samples on filters had no influence on cell physiological condition [9].…”
Section: Methodsmentioning
confidence: 87%
“…The duration of each measurement was 60 s. The DF kinetics reflected changes in emission intensity on a time scale of 0.1-0.9 ms in the intervals between actinic light pulses. Characteristics and the protocol of measurements with an M-PEA-2 instrument have been described in detail previously [6,8,9].…”
Section: Methodsmentioning
confidence: 99%